Administrasi Pendidikan sebagai Strategi Manajemen Sumber Daya dan Pendorong Efisiensi Operasional untuk Memperkuat Kinerja Sekolah - Azizah, Wala; Neneng Ulfiyah (Journal of Practice Learning and Educational Development, 2025)
Educational administration plays a crucial role in managing resources and improving operational efficiency in schools. With the growing demand for better school performance, optimizing administrative strategies is essential. Purpose: This research explores educational administration as a resource management strategy to drive operational efficiency and enhance school performance. Methods: A mixed-methods approach was used, combining qualitative and quantitative data collected through surveys, interviews, and focus groups involving school administrators, teachers, and stakeholders. Results: The study found a positive correlation between effective resource management and operational efficiency, leading to a 25% increase in student achievement in schools that implemented structured strategies. Conclusions: Effective educational administration as a resource management strategy is vital for operational efficiency and better school outcomes. Collaboration between administrators and teachers and integrating technology are key success factors. Contributions: The research offers insights for education leaders and policymakers on the importance of resource management to improve school performance, serving as a foundation for better administrative policies and practices.